Strengthening farmer participation in climate policy: Taking advantage of policy intervention opportunities - Chevallier, Romy; Chesterman, Sabrina (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
It is imperative that NFOs are proactively engaged in the policy cycle from the outset, and for the duration of the process, until implementation and monitoring. To do this, NFOs need to be aware of who to engage, how to engage and what strategic assess options there are available to them for strategic policy intervention. This will ultimately strengthen the legitimacy and ownership of climate policies for farmers in the region.